Rezeption biblischerTexte im "religiösen Gedächtnis": Bedeutung biblischer Texte in Spannung von Ursprung und Aktualität - Mallmann, Bernard (Estudios bíblicos, 2021)
Biblical hermeneutics strives for the right interpretation of the texts, which are said to have meaning for theology and life. Besides the historical-critical exegesis, the aesthetics of reception in its plurality is more and more included in biblical hermeneutics. The arride explores the role of a religious community in the reception of biblical texts. In the ,,religious memory" a religious community does not only pass on biblical texts, but finds its identity assurance in the tension between origin and constant actualization. Thus the community enters into the process of canonization of biblical texts by opening the future in the biblical canon and its memory. But the biblical canon and identity of faith are based on nothing other than the revelation of God.